The negative existential cycle in Bantu - Bernander, Rasmus; Gibson, Hannah; Devos, Maud (My University, 2022)
Renewal of negation has received ample study in Bantu languages. Still, the relevant literature does not mention a cross-linguistically recurrent source of standard negation, i.e., the existential negator. The present paper aims to find out whether this gap in the literature is indicative of the absence of the Negative Existential Cycle (NEC) in Bantu languages. It presents a first account of the expression of negative existence in a geographically diverse sample of 93 Bantu languages. Bantu negative existential constructions are shown to display a high degree of formal variation within both dedicated and non-dedicated constructions. Although such variation is indicative of change, existential negators do not tend to induce changes at the same level as standard negation. The only clear cases of the spread of an existential negator to the domain of standard negation in this study appear to be prompted by sustained language contact.
Keywords: Bantu languages; Morphology; negation